2018
DOI: 10.1002/aic.16177
|View full text |Cite
|
Sign up to set email alerts
|

Co‐doped ZnO thin films grown by pulsed electron beam ablation as model nano‐catalysts in fischer‐tropsch synthesis

Abstract: A single-step deposition of cobalt-doped zinc oxide (Co-ZnO) thin film nano-composites on three different crystalline substrates, viz., Al 2 O 3 (c-sapphire), silicon (100) (Si), and SiO 2 (quartz) is reported, using pulsed electron beam ablation (PEBA). The results indicate that the type of substrate has no effect on Co-ZnO films stoichiometry, morphology, microstructure, and film thickness. The findings show the presence of hexagonal close-packed metallic Co whose content increases in the films deposited on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Sometimes, a combination of known methods is employed, which may involve precipitation and/or impregnation steps [ 18 ], or co-precipitation of the metal salts [ 19 ]. Other catalyst preparation methods include electrospinning [ 20 ], ion-exchange [ 21 ], pulsed electron beam ablation (PEBA) [ 22 ], carbon-vapor deposition (CVD) [ 23 ], and the spray-drying technology [ 24 ]. In other works, the single roller melt-spinning method has been used, which involves in situ carbidation through rapid quenching of skeletal nano-crystalline Fe [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, a combination of known methods is employed, which may involve precipitation and/or impregnation steps [ 18 ], or co-precipitation of the metal salts [ 19 ]. Other catalyst preparation methods include electrospinning [ 20 ], ion-exchange [ 21 ], pulsed electron beam ablation (PEBA) [ 22 ], carbon-vapor deposition (CVD) [ 23 ], and the spray-drying technology [ 24 ]. In other works, the single roller melt-spinning method has been used, which involves in situ carbidation through rapid quenching of skeletal nano-crystalline Fe [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby the surface topography can be constructed even down to an atomic resolution. For instance, Ali et al used AFM to characterize surface morphology and roughness in the study of Co-doped ZnO films grown on various crystalline substrates in Fischer-Tropsch synthesis and revealed that the Co-ZnO films consisted of well-isolated nano-globules [70]. LEIS is mainly used to study relative positions of atoms in a surface lattice and chemical composition of sample surface by shooting ions (normally ionized noble gas atoms or alkali atoms) to the sample surface and observing positions, velocities, and energies of the scattered ions [71].…”
Section: Experimental Approach For Studying Active Sitesmentioning
confidence: 99%